(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The development of medication delivery technology has led to an increase in the popularity of pediatric formulations. However, there is absence of secure and efficient drug delivery mechanism for pediatric patients. It is crucial to design and create a novel and suitable delivery system to guarantee precise and reliable medication administration to pediatric patients, as their pharmacokinetics and pathophysiologic profiles differ from those of adults. Under this heading, discussion will be carried out in order to increase stability; new medication delivery techniques and technology are being developed to enhance the stability, toxicity, flexibility, moreover secure aspects of pediatric oral formulations. Specifically, issues with patient acceptability and manufacturability are discussed in this section, and innovative medication delivery methods are examined to address current issues.